A Dynamic Methodology for Embedding Generative System Approaches in Architectural Design Education - Gürer, Ethem; Alaçam, Sema; Çağdaş, Gülen (ICONARCH International Congress of Architecture and Planning, 2012)
The generative systems have been discussed in many fields such as computer science, architecture, natural and social sciences over the last fifty years. Different approaches such as Cellular Automata (CA), Agent Based Design (ABD), Swarm Intelligence, Genetic Algorithms (GAs), L-Systems (Ls), Bio-Mimetics (B) within generative design paradigm show a potential to enrich way of thinking, particularly in architecture. However, generative design accompanied with computational thinking has not been embedded enough into the architectural curriculum. In this paper, we focus both on discussing how to introduce generative design theories to the students of architecture and how to observe the short term reflections via students’ term projects.